(untitled) (Journal of Academic Research, 2022)
Diabetic patients may experience a variety of complications, including immunodeficiency, blood ischemia and microbial infections, which can increase the risk of diabetic foot wounds becoming chronic and difficult to treat. Diabetic foot patients are subjected to long periods of antimicrobial therapy, which leads to an increase in antibiotic-resistant strains. Multidrug resistance organisms have spread throughout the world in diabetic foot infections (DFIs). This type of infection requires prompt and effective antimicrobial therapy to reduce the complications associated with such infections. The detection rate and identification of common microbial pathogens, as well as their antimicrobial susceptibility patterns, were the focus of this study in DFIs. Forty swabs (specimens) were collected from none repeated diabetic foot patients attending MMC for medical services. Standard microbiological methods were used to identify microbial pathogens. The Clinical and Laboratory Standards Institute’s standard guidelines were used to determine antimicrobial susceptibility testing and resistant profiles (CLSI). According to the study’s findings, bacterial growth was found in 80 % of the specimens. Staphylococcus aureus (30%) and Pseudomonas aeruginosa (22.5%) were the most frequently isolated bacterial pathogens. Gram-positive isolates were generally highly sensitive to Cefuroxime (72%), Azithromycin (61%), and Clindamycin (57 %). There was a high MRSA prevalence (75 %). The majority of Gram-negative isolates were susceptible to Azithromycin (63%) and Amikacin (59%), but highly resistant to Augmentin (81%) and Ceftriaxone (63%). DFIs are common cases in MMC’s surgery OPD, and the majority of them are associated with multi-drug resistant strains.